Aneurysmal subarachnoid hemorrhage and primary decompressive craniectomy: management guidelines based on 13 years of experience at a referral center - Martínez, Silvina A.; Montilla, Flor; Guevara, María; Frascarolli, Sebastian; Martin, Clara; Rubino, Pablo (Revista Argentina de Neurocirugía, 2025)
Background: decompressive craniectomy is an effective therapeutic tool for controlling intracranial hypertension, indicated both primarily based on clinical and imaging predictors, and later when hypertension becomes refractory. In the context of aneurysmal subarachnoid hemorrhage, hypertension may present immediately or delayed, associated with cerebral edema, hydrocephalus, hematomas, or infarcts due to vasospasm. In cases requiring urgent microsurgical clipping, the decision to combine decompressive craniectomy should be based on clinical status, preoperative imaging, and intraoperative findings, without delaying treatment of the ruptured aneurysm. Objectives: to evaluate the indication for primary decompressive craniectomy in patients with subarachnoid hemorrhage undergoing microsurgical clipping and to identify predictors of early reintervention and their impact on functional outcome. Methods: retrospective analysis of patients with SAH admitted to our center between 2011 and 2024 treated with clipping and requiring decompressive craniectomy either primary or within 48 hours of clipping. Management was analyzed in each case. The Chi-square test or Fisher’s exact test was used, as appropriate, to establish the association between variables. Functional outcome was assessed at 6 months using the modified Rankin Scale (mRS). Results: a total of 113 SAHs treated with clipping required decompressive craniectomy within the first 48 hours: 87.6% primary and 12.4% secondary. The indication was associated with poor neurological grade, presence of hydrocephalus, hematoma with mass effect, and brain herniation at the time of surgery. The presence of a hematoma with mass effect, poor neurological grade, and brain herniation at the end of clipping were statistically significantly associated with an unfavorable mRS. A "relaxed" brain at the end of clipping may underestimate cerebral edema and must be contextualized with other variables. Conclusion: we present the institutional approach as a guideline for the management of these cases. This subgroup of patients is associated with high morbidity and mortality, so early identification of candidates for decompressive craniectomy could significantly modify their clinical course.